The education coaching concept - Borova T.A (Kharkov National Pedagogical University, 2011)
The article deals with education coaching concept in the context of higher education. The main coaching and concept definitions are analyzed. The education coaching definition is given. The main ideas, principles and methodology approaches to the education coaching concept are identified and characterized. It is grounded the methodological approaches that are the basis of the educational coaching concept. The main points of education coaching are summarizes. The aim of education coaching is defined as professional self-development university teachers' staff and their self-realization.